Anti-spalling fibers for refractory castables: A potential application for recycling drinking straws. Issue 9 (15th June 2020) - Salomão, R.; Pandolfelli, V.C.
Abstract: Disposing plastic after using is an urgent worldwide issue, and recycling is usually pointed out as the best solution. Recycled thermoplastic polymers, however, in most cases, present inferior properties when compared to their as-produced equivalent grades. Re-exposure to processing temperatures and intense shear results in significant thermo-mechanical-oxidative degradation of the polymeric material. Typical consequences lead to a reduction in the average molecular mass and melting temperature, and modifications in the composition, microstructure and rheological behavior. Although such effects usually hinder using these materials in their original application, other technological uses can be found. In the present paper, a methodology used to produce thin continuous fibers from recycled polypropylene (PP) and high-density polyethylene (HDPE) drinking straws is presented. The processing parameters for melt-extrusion and chopping the fibers were set to produce staples of similar length and diameter as the conventional PP fibers currently employed as anti-spalling additives during the first heating of self-flow refractory castables. Because of their lower melting temperature and high melt flow index, recycled polymers cannot be used to produce new straws, however the fibers produced with them increased the castables' permeability at lower temperatures than those observed for the conventional ones. Therefore, besides helping the environment, the castables' overall risk of explosive spalling and total drying time can be successfully reduced.